Emotion-Focused Therapy's Empty-Chair Task for Complicated Grief: An Open Trial. - Gamoneda, José; Jódar, Rafael; Timulak, Ladislav (Journal of Loss & Trauma, 2026)
The Empty-Chair Task for Unfinished Business has been studied in the context of treatments for trauma, depression and anxiety and the literature explicitly talks about its potential for bereavement processes. However, it has not yet been studied as an intervention for complicated grief. The present preliminary study takes the form of an open trial, in which participants received a brief individual therapy consisting of three sessions addressing complicated grief. In the second session, the task was applied, and changes in symptoms were measured at the end of treatment and during follow-up. Additionally, a process-outcome study was conducted to examine whether the degree of resolution of emotional processes in the Empty-Chair Task with the deceased, predicts changes in outcomes. The intervention was delivered as a teletherapy on a sample of 26 individuals. The study revealed significant improvements (with large pre-post and follow-up effect sizes) in symptomatology post-intervention, and particularly at a two-month follow-up. Clinically significant changes were also observed, increasing to 36% in the follow-up. The results also showed that the in-session task resolution of Unfinished Business predicted an improvement in grief symptomatology both at post-intervention and follow-up. Overall, this study underscores the potential value of this task for complicated grief, highlighting the importance of emotional processing, providing valuable insights for clinical practice.